Clinical advances in antibody-drug conjugates for hematological malignancies - TANG Sijie; MI Jianqing (Shanghai Jiaotong Daxue xuebao. Yixue ban)
An antibody-drug conjugate (ADC) is a targeted therapeutic drug composed of a monoclonal antibody linked to a small-molecule cytotoxic drug via a linker. Once administered, ADCs bind to tumor-specific antigens, forming ADC-antigen complexes, which are internalized through endocytosis. The linkers are then cleaved via endosomal-lysosome pathway and the cytotoxic drug is released, which induces apoptosis in the target cells. ADCs combine the advantages of monoclonal antibody drugs and cytotoxic drugs. They are able to reduce damage to normal cells while killing target cells, thus exhibiting higher anti-tumor efficiency. As the treatment of hematological malignancies gradually advances into the era of targeted immunotherapy, ADCs, as one of the hot spots, have shown broad prospects and also face many challenges in drug development and clinical application. Currently marketed ADCs in China include brentuximab vedotin (anti-CD30), inotuzumab ozogamicin (anti-CD22) and polatuzumab vedotin (anti-CD79B), while those marketed abroad include gemtuzumab ozogamicin (anti-CD33) and loncastuximab tesirine (anti-CD19), all demonstrating good efficacy and safety in clinical practice. Additionally, ADCs targeting different antigens such as CD123, CD19, CD20, receptor tyrosine kinase-like orphan receptor 1 (ROR1), and CD38 are undergoing clinical studies. Globally, there are over a hundred ADCs in development, and it is hoped that more breakthroughs will be achieved in the future to further optimize the treatment strategies for hematologic malignancies.